Linear Equation Method of Constructing Confounding Plan in pn - Factorial Experiment (Dhaka University Journal of Science, 2012)
This article describes a linear equation method of designing simultaneous confounding of one or more factorial effects in pn - factorial experiment. It is demonstrated that it becomes easier to construct the design of simultaneous confounding of one or more factors in a pn - factorial experiment especially when the number of factors as well as the number of levels becomes larger. It is also discussed that such approach is very much convenient from the viewpoint of computation.DOI: http://dx.doi.org/10.3329/dujs.v60i1.10338Dhaka Univ. J. Sci. 60(1): 61-64 2012 (January)